KAJIAN AKTIVITAS ANTIOKSIDAN DAN ANTIMIKROBA EKSTRAK BIJI, KULIT BUAH , BATANG DAN DAUN TANAMAN JARAK PAGAR (Jatropha curcas L.) - Setyaningsih, Dwi; Nurmilah, Ovi Yulianti; Windarwati, Sri (REKAPANGAN, 2010)
Jatropha  curcas is  one  of  potential  bioenergy  plant.  Jatropha  curcas  also  has  great potential  for  the  development  of  bio-products,  medicines  and  consumer  good  since  it contains some bioactive agents such as β-sitosterol, stigmasterol, curcin, flavonoid and 12-deoxyl-16-hydroxyphorbol  (phorbol  esther)  that  potentials  as  antioxidant  and antimicrobial  agent.  The  purpose  of  this  research  were  to  determine  the  yield  of extract, antimicrobial and antioxidant activity from seed, fruit shell, stem and leaves of  J. curcas. Seed, fruit shell, stem and blend of stem and leaves were extracted with three type  of  solvents.  They  were  methanol,  ethyl  acetate  and  n-hexane.  From  the  yield  of extract,  it  could  be  concluded  that  seed  of J.curcas L  contained  a  lot  of  semi  polar compounds  (35,98%)  and  non  polar compounds  (32,27%),  blend  of  stem  and  leaves contained a lot of polar compounds (9,75%) and J. curcas fruit shell contained a lot of polar  compounds  (5,96%).  Antioxidant  activity  with  scavenging  effect  on  DPPH radical  (1,1-diphenyl-2-picrylhidrazil)  and  antimicrobial  activity  using  well  diffusion method  showed  that  methanol  extract  from J.  curcas seed  had  the  highest  value  of antioxidant  and  antimicrobial  activity  than  other  samples.  The  antioxidant  activity  of methanol  extract  from J. curcas seed  was  93,40%,  comparable  with  ascorbic  acid  as reference. The potency of antimicrobial activity of this extract  could be seen from the bacterial inhibition zone diameter of 11.9 mm for E. coli and 14.83 mm for S. aureus.Keywords: Antimicrobial, antioxidant, Jatropha curcas L